2016
DOI: 10.1016/j.cell.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Improves Glucose Homeostasis through IKKβ-XBP1s Interaction

Abstract: SUMMARY It is widely believed that inflammation associated with obesity has an important role in the development of type 2 diabetes. IκB kinase beta (IKKβ) is a crucial kinase that responds to inflammatory stimuli such as Tumor Necrosis Factor α (TNFα), by initiating a variety of intracellular signaling cascades, and is considered to be a key element in the inflammation-mediated development of insulin resistance. We show here, contrary to expectation, that IKKβ-mediated inflammation is a positive regulator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 45 publications
(68 reference statements)
6
86
2
2
Order By: Relevance
“…We also found that IKKβ phosphorylation of BAD is important for adipocyte survival in obesity (34). A recent study demonstrated that IKKβ can phosphorylate XBP1 to regulate glucose homeostasis in the liver (57). We and others previously demonstrated that IKKβ affects β-catenin ubiquitination and degradation in different cell types (7,18,38), but the precise mechanisms have not been elucidated.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We also found that IKKβ phosphorylation of BAD is important for adipocyte survival in obesity (34). A recent study demonstrated that IKKβ can phosphorylate XBP1 to regulate glucose homeostasis in the liver (57). We and others previously demonstrated that IKKβ affects β-catenin ubiquitination and degradation in different cell types (7,18,38), but the precise mechanisms have not been elucidated.…”
Section: Discussionmentioning
confidence: 84%
“…Although much attention has been focused on the NF-κB-dependent functions of IKKβ, IKKβ can regulate inflammation, apoptosis, cell proliferation, and metabolic homeostasis through NF-κB-independent mechanisms by phosphorylating other key molecules such as SNAP-23, IRF7, p53, BAD, and XBP1 (39,40,57). For example, IKKβ can inhibit cell death in an NF-κB-independent manner by phosphorylating BAD, a BH3-only proapoptotic protein, to prime it for inactivation (40).…”
Section: Discussionmentioning
confidence: 99%
“…sXBP1 protein was detected in the nuclear extract of DCs, but its expression did not show significant changes upon various treatments nor in the presence of MKC8866 (Figure 8B). 2-DG increased the binding of sXBP1 to the three X-boxes in the IL23A promoter (Figure 8C), which suggests the involvement of this transcription factor in the enhancement of IL23A expression and that in addition to the expression of the protein, either posttranslational modifications (48, 49) or formation of an enhanceosome with other factors may be necessary for full development of transcriptional activity (50). Since sXBP1 also plays a central role in the control of the hexosamine biosynthetic pathway by regulating the expression of GFPT1 (51), the expression of this enzyme and the binding of sXBP1 to an X-box placed 147 bp upstream of the transcription initiation nucleotide were addressed.…”
Section: Resultsmentioning
confidence: 94%
“…XBP1s directs the transcription of a wide range of targets including the expression of chaperones, foldases and components of the ERAD pathway, in order to relieve ER stress and restore homeostasis [109,110]. However, XBP1s can also participate in the regulation of numerous metabolic pathways such as lipid biosynthesis [111][112][113], glucose metabolism [114][115][116][117][118], insulin signalling [117,119,120], redox metabolism [121], DNA repair [122] and it influences cell fate including cell survival [123], cell differentiation [124][125][126][127][128] and development [126,[129][130][131]. Although there is strong evidence pointing to a key role for XBP1 in multiple cellular functions, the exact mechanisms by which XBP1 mediates gene transactivation are still elusive.…”
mentioning
confidence: 99%